Human pregnancy and birth: The enrichment of a booklet with medicinal plants for postpartum wellness - Wiwik Hartika; Ruqiah Ganda Putri Panjaitan; Andi Besse Tenriawaru (University of Muhammadiyah Malang, 2024)
The complexity of the reproductive system necessitates instructional media to facilitate comprehension, as its processes unfold internally and are not readily observable. This study aims to assess the viability of booklet sub-materials on fertilization, gestation, and childbirth, derived from the inventory findings of medicinal plants for postpartum care, as educational resources. The research and development used the Borg & Gall model which included identifying potential problems, data collection, product design, design validation, and product revision. The booklet media underwent validation by five validators using validation sheets, while the evaluation criteria encompassed format, content, and language proficiency. The validation data were analyzed using CVR (Content Validity Ratio) and CVI (Content Validity Index). The results of the booklet media validation obtained a CVR value on each criterion of 1.00 with a valid category and a CVI value of 1.00 with a valid category. The booklet on the subject of gestational fertilization and childbirth from the results of the inventory of medicinal plants for postpartum is suitable for use as a learning media.